PRODUK ABON JANTUNG PISANG SEBAGAI SALAH SATU SOLUSI PENDAPATAN ALTERNATIF KELUARGA - Handriyani Dwilita; Pipit Buana Sari (Jurnal Abdi Ilmu, 2021)
The service was carried out in Dusun 20, Klambir Lima Kebun Village, as the object of implementation, namely housewives. This service carries the processed banana heart (banana flower) into shredded with various flavors. Banana plants are very easy to find around us, even the results of this plant in the form of bananas are one of the foods that are in demand. In addition to bananas, banana plants also produce banana leaves and flowers as agricultural commodities that are worth selling. However, discarding bananas or banana hearts can be processed into very delicious, nutritious and even selling food, one of which is shredded banana heart. This preparation is the main topic of community service activities in 20 hamlets of Klambir Lima Kebun village. The service method used is socialization, training and mentoring. The results of this activity can add insight to housewives about the existence of alternatives to processed banana flowers/hearts that are worth selling.